The Effects of Different Types of Exercise on Pulmonary Inflammation and Fibrosis in Mice with Type 2 Diabetes Mellitus - Haoyang Gao; Xiaotong Ma; Ze Wang; Danlin Zhu; Yifan Guo; Linlin Zhao; Weihua Xiao (Cells, 2025)
Background: Diabetic lung disease, characterized by inflammation and fibrosis, is an emerging chronic complication of type 2 diabetes mellitus (T2DM). However, systematic studies on the effects of exercise interventions remain limited. This study aimed to investigate the impact of different exercise types (swimming, resistance training, and high-intensity interval training [HIIT]) on pulmonary inflammation and fibrosis in T2DM mice, and to explore underlying molecular mechanisms. Methods: A T2DM mouse model was established by a high-fat diet (HFD) combined with streptozotocin (STZ) induction. Mice were randomly divided into sedentary control, swimming, resistance training, and HIIT groups, and underwent 8 weeks of exercise intervention. After the intervention, body composition was assessed. Lung histopathological changes were evaluated by hematoxylin&eosin (HE) and Masson staining. Inflammatory cytokines, fibrosis markers, and the expression of the TGF-β1/Smad signaling pathway were detected. Macrophage infiltration and polarization were also analyzed. Results: Exercise intervention improved body composition and reduced oxidative stress in T2DM mice. All three exercise modalities downregulated inflammatory cytokine expression, inhibited macrophage activation and M1 polarization, and promoted M2 polarization. Additionally, exercise improved lung tissue structure, reduced collagen deposition, and decreased the expression of fibrosis-related markers. Furthermore, anti-fibrotic effects were mediated by suppression of the TGF-β1/Smad signaling pathway and inhibition of epithelial-mesenchymal transition (EMT). Among the interventions, HIIT demonstrated the strongest inhibitory effect on the TGF-β1/Smad pathway, while swimming showed the most significant anti-inflammatory benefits. Conclusions: Different types of exercise effectively alleviate pulmonary inflammation and fibrosis in T2DM mice. These effects are closely related to the inhibition of oxidative stress, regulation of macrophage polarization, and suppression of TGF-β1/Smad signaling activation, with swimming and HIIT demonstrating superior protective benefits.